Rationale, design and methodology of APPROACH-IS II: International study of patient-reported outcomes and frailty phenotyping in adults with congenital heart disease. (15th September 2022) - Van Bulck, Liesbet; Kovacs, Adrienne H.; Goossens, Eva; Luyckx, Koen; Zaidi, Ali; Wang, Jou-Kou; Yadeta, Dejuma; Windram, Jonathan; Van De Bruaene, Alexander; Thomet, Corina; Thambo, Jean-Benoît; Taunton, Marshall; et al.
Abstract: Background: In recent years, patient-reported outcomes (PROs) have received increasing prominence in cardiovascular research and clinical care. An understanding of the variability and global experience of PROs in adults with congenital heart disease (CHD), however, is still lacking. Moreover, information on epidemiological characteristics and the frailty phenotype of older adults with CHD is minimal. The APPROACH-IS II study was established to address these knowledge gaps. This paper presents the design and methodology of APPROACH-IS II. Methods/design: APPROACH-IS II is a cross-sectional global multicentric study that includes Part 1 (assessing PROs) and Part 2 (investigating the frailty phenotype of older adults). With 53 participating centers, located in 32 countries across six continents, the aim is to enroll 8000 patients with CHD. In Part 1, self-report surveys are used to collect data on PROs (e.g., quality of life, perceived health, depressive symptoms, autonomy support), and explanatory variables (e.g., social support, stigma, illness identity, empowerment). In Part 2, the cognitive functioning and frailty phenotype of older adults are measured using validated assessments. Discussion: APPROACH-IS II will generate a rich dataset representing the international experience of individuals in adult CHD care. The results of this project will provide a global view of PROs and the frailty phenotype of adults with CHD and will thereby address important knowledge gaps. Undoubtedly, the project will contribute to the overarching aim of improving optimal living and care provision for adults with CHD. Highlights: The variability of patient-reported outcomes in adults with congenital heart diseases (CHD) is not fully understood yet. Available information on the frailty phenotype of older adults with CHD is minimal. The research project APPROACH-IS II will establish these knowledge gaps. APPROACH-IS II is a cross-sectional global study in which 53 centres from 32 countries participate.